Risk disclosure: Analyzing the determinants of risk disclosure in the annual reports of UK and Hong Kong companies - XUE, MEI (2013)
Abstract Risk and risk management have been given a considerable attention because of the complexities in the business world. The aim of this report is to analysis the difference of risk disclosure determinants between companies from UK and Hong Kong. This study seeks to address the gap in the literature of cross-country study. And it explores risk disclosure within 80 annual reports using self-conduct risk disclosure index and regression analysis. The paper confirmed a significant relationship between the number of risk disclosure and company size for both countries. It also found a significant difference between banks and nonbanks. Banks disclose more risk information than nonbanks. Moreover, it also confirmed a fairly significant association between the profitability and risk disclosure index. However, no association is found between gearing ratio and risk disclosure index. The results show no difference between UK and Hong Kong companies on risk disclosure. Oil companies are also not found to disclose more risk information than other companies. One key limitation of this report concerns on the calculation of risk disclosure index or whether it is the best way to present the risk in this report. In addition, the subjective judgment cannot be wholly avoided when read the risk management chapter of the annual report and the selection of the nine risk categories is subject to debate. Overall, the results of this report are effective in making important contributions to the existing literature. In order to inform the debates and ensure the outcomes are appropriate, the additional further research to this topic is still necessary. The future work may use other approaches to measuring the relationship between the risk disclosure and leverage, country and oil industry within this study. The cross-country and industry-specified risk disclosure studies could be helpful in understanding the determinants and affection of the risk disclosure.